PERAN PEMIMPIN GABUNGAN KELOMPOK TANI DI KELURAHAN KARANGREJO KECAMATAN SUMBERSARI KABUPATEN JEMBER - Ilham Ainun Gibran; Augustrie Naufal H; Sakinah Rahmaniyah (SOCA: Jurnal Sosial Ekonomi Pertanian, 2018)
Agriculture is a sector that supports Indonesian's economy. The study aims to determine the leader role of a farmer group in Karangrejo Village, Sumbersari Subdistrict, Jember Regency. The data collection method in this study uses primary and secondary data. The data analysis method in this study uses the Miles and Huberman analysis model with data collection, data reduction, data display, andconclusions or verification. Data collection was carried out using a case study to explain the leader role of a farmer group in the Karangrejo Village, Sumbersari Subdistrict, Jember Regency. The results show that the ineffectiveness of the performance of the head of the Karangrejo Village Gapoktan because the position held could not be done separately for a group of farmers under the auspices of the Gapoktan in Karangrejo Village, Sumbersari Subdistrict, Jember Regency.